Pengaruh Model Pembelajaran Edutainment Terhadap Minat Belajar IPS di SMPN 1 Tigaraksa, Kabupaten Tangerang: The Influence of Edutainment Learning Model on the Interest in Learning Social Studies at SMPN 1 Tigaraksa, Tangerang Regency - Primawardani, Astried Thaliana; Hasriani, Hasriani (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
This study aims to examine the effect of the edutainment learning model on the learning interest of eighth-grade students at SMPN 1 Tigaraksa, Tangerang Regency. The research employs a quasi-experimental method with a non-equivalent control group design. A total of 80 students participated, with 40 students in the control class using the lecture method and 40 students in the experimental class using the edutainment model. Data were collected through observation, documentation, and a learning interest questionnaire, and then analyzed using SPSS for Windows 24. The independent sample t-test results showed a significance value of 0.000 < 0.05, with the average learning interest score being 78.66 in the experimental class and 72.37 in the control class, indicating a significant difference in learning interest between the two classes. The implementation of the edutainment model's learning interest aspects is suggested as the key factor contributing to this increase.